SISTEM INFORMASI PENJADWALAN RUANG KELAS PERKULIAHAN BERBASIS WEB MENGGUNAKAN WATERFALL MODEL PADA INSTITUT BISNIS MUHAMMADIYAH BEKASI - Afri Yudha; Muhammad Ihya Aulia Elfatiha (Jupiter: Journal of Computer & Information Technology, 2021)
Information technology in universities is already a primary necessity. Universities are required to provide optimal services to students, one of which is scheduling lecture rooms. Research on the scheduling of lecture classrooms at The Muhammadiyah Bekasi Business Institute is still done manually, a factor related to the manual system is the lack of efficiency and precision in its work so that it is not uncommon to share the intersected rooms. Software development method using Software Development Life Cycle Waterfall Model. Field direct observation data collection techniques, system development tools using UML (Unified Modeling Language), programming languages using PHP, HTML, CSS, Javascript, and Jquery, server-side scripting using MySQL databases. The result of this research is an information system of scheduling lecture rooms that is able to manage to schedule, especially in the division of lecture space and facilitate academic personnel in the preparation of schedules, more flexible and efficient, harmony and sustainable.